Excretory-Secretory Products from Hookworm L3 and Adult Worms Suppress Proinflammatory Cytokines in Infected Individuals - Stefan Michael Geiger; Ricardo Toshio Fujiwara; Paula Albuquerque Freitas; Cristiano Lara Massara; Omar dos Santos Carvalho; Rodrigo Corrêa-Oliveira; Jeffrey Michael Bethony (Journal of Parasitology Research)
We compared the effects of larval and adult worm excretory-secretory (ES) products from hookworm on the proliferative responses and cytokine secretion in peripheral blood mononuclear cells (PBMCs) from hookwormpatients and egg-negative, nonendemic controls. When compared with negative controls, mitogen-stimulated PBMC from hookworm-infected individuals showed a significantly reduced proliferative response when adult worm ES antigen was added to the cultures. Furthermore, in hookworm-infected individuals a significant downmodulation of inflammatory interleukin (IL)-6 and tumor necrosis factor (TNF)-α secretion resulted when PBMCs were stimulated with mitogen in combination with larval or adult worm ES. Both, interferon (IFN)-γ and IL-10 secretion were significantly lower in stimulated PBMC from infected individuals; however the IFN-γ/IL-10 ratio was much lower in hookworm-infected patients. Comparable effects, although at lower concentrations, were achieved when PBMCs from both groups were incubated with living hookworm third-stage larvae. We suggest that hookworm ES products downmodulate proliferative responses and inflammation during the chronic phase of the disease and facilitate early larval survival or adult worm persistence in the gut.